Wood and bark of Pinus halepensis as archives of heavy metal pollution in the Mediterranean Region. (August 2018) - Rodríguez Martin, José Antonio; Gutiérrez, Carmen; Torrijos, Manuel; Nanos, Nikos
Abstract: Natural levels of heavy metals (HM) have increased during the industrial era to the point of posing a serious threat to the environment. The use of tree species to record contamination is a well-known practice. The objective of the study was to compare HM levels under different pollution conditions: a) soil pollution due to mining waste; b) atmospheric pollution due to coal-fired power plant emissions. We report significant HM enrichment in Pinus halepensis tissues. Near a burning power plant, Pb content in a tree wood was 2.5-fold higher that in natural areas (no pollution; NP). In mining areas, Cd content was 25-fold higher than NP. The hypothesis that HM contents in tree rings should register pollution is debatable. HM uptake by pines from soil, detoxification mechanisms and resuspended local soil dust is involved in HM contents in wood and bark. Graphical abstract: Image 1 Highlights: Pinus halepensis trees as bioindicators of HM pollution. Tree rings and tree barks as tissues to evaluate environmental contamination. Mining waste and coal-fired power plant emissions as sources of pollution. Tree rings as a retrospective analysis of HM accumulation in P. halepensis . Abstract : Tree rings and bark of Pinus halepensis are used to evaluate heavy metal pollution and to compare the past and the present-day under different soil conditions.